Children and youth in armed conflict : responses, resistance, and portrayal in media - Shah, Tamanna M. (Sociological studies of children and youth ;, 2024)
This book contains an Open Access chapter. The integration of new technologies has opened unparalleled opportunities for shaping the discourse of marginalized groups and facilitating decentralized communication during crises. Yet, a divide exists between individual experiences and societal perceptions and how these narratives are portrayed and perceived in the media. These dynamics form the basis of exploration in Children and Youth in Armed Conflict: Responses, Resistance, and Portrayal in Media, the second of two volumes, offering a compelling exploration of how children and youth endure conflict and how their stories are told and retold in the public sphere, influencing advocacy, policymaking, and community responses worldwide. The second volume examines diverse global perspectives of media use by post-war generations in Bosnia-Herzegovina, Kosovo, Montenegro, and Serbia. It explores cybersecurity, AI, and their impact on children in conflict, analyzes narratives in art and online memorials, children's agency in Ukraine and Syria, and investigates social media's role in youth activism in India and Israel-Palestine. Chapters highlight issues such as Boko Haram's impact on girls through media representation, social media narratives in the Israel-Palestine conflict, China's portrayal in films, and the analysis of children's art and poetry within conflict zones. Acknowledging the crucial role of children and youth as catalysts for peace and justice in conflict and post-conflict settings, this is pathbreaking reading for scholars of childhood, youth, peace, and conflict.